PRETEND PLAY, FANTASY AND CREATIVE PROCESSES WITH PRESCHOOL CHILDREN - Gardašević, Ana; Gardašević, Ana (Studies in Teaching and Education, 2025)
The paper is about the importance of the influence od pretend play and fantasy on creative, cognitive processes, emotional connestion and building relationships with others. In order to observe creativity, cognitive, affective and interpersonal relationships, pretend play anda fantasy are analysed in the paper. By analysing the narrative stories of children"s play, divergent thinking, flexibility od reality, fluidity and originality of ideas, symbolism, fantasy, non-patterned behaviour and intellectual initiative were observed, which affect the child"s creativity and better preparedness for new life situations. The paper points out the importance of creating conditions for the development of pretend play and fantasy by adults. The results highlight how important developing the practice of supporting children"s play is for strengthening creativity, sognitive processes, emotions and relationships that are built among participants in the game.